Risco ecológico da pesca de atuns e afins em cardumes associados no Atlântico Oeste - Cavalcante, Juliana Vanessa da Cunha (2018)
In Brazil, tunas and tuna-like species are of fundamental commercial importance for the country and have favored the development of the fishing industry. Among all exploited species of this genus, some of them have a special place on the catchings, such as: bigeye tuna (Thunnus obesus), yellowfin tuna (Thunnus albacares), albacore (Thunnus alalunga) and skipjack tuna (Katsuwonus pelamis) that represents 68% of all the world production of tunas and tuna-like species. Ecological risk analysis consists of a process that analyzes the likelihood of adverse ecological effects being caused by exposure to one or more stressors. The purpose of this study was to carry out the ecological risk analysis for the fishery of and tuna-like species in Porto dos Barcos, located in the municipality of Itarema, west coast of the state of Ceará. The ecological risk analysis included a sampling effort of twelve field trips to Itarema - Ceará from October 2016 to September 2017. This analysis consisted of three levels. Level 1, Consequence, Intensity and Scale Analysis (SICA), which is a qualitative approach. The components of the SICA, which at the end of the evaluation, obtained a score greater than / equal to three, were submitted to the second phase of the analysis, Productivity and Susceptibility Analysis (PSA). The PSA is more focused on the components with greater risk by the activity. After the analysis of productivity and susceptibility, the components that were considered with medium and high risk, it is suggested the elaboration of management measures that can help the management and the reduction of these risks. The tuna fishery in Itarema is considered to be a recent activity, since it began in the present decade around year 2013. In this fishery, boats with an average length of 14.3 ± 1.11 are used. Three species of tuna were identified as the target of the fishery: yellowfin tuna (Thunnus albacares), bigeye tune (Thunnus obesus) and skipjack tuna (Katsuwonus pelamis). PSA's final score values ranged from 1.91 to 2.96. Risk levels varied between low to medium. The lowest risk value recorded was the Skipjack and the highest value was for Bigeye. Therefore, it suggests researches to be conducted in order to support management measures for this species. Keywords: Fishing resource. Ecology, Management.